Metode Evaluasi Program Kesehatan Ibu dan Anak di Kabupaten Sigi, Provinsi Sulawesi Tengah - Lexy Kareba; Saiful A; Parmi; Fitri Arni; Desak Susianawati (Journal of Innovative and Creativity, 2025)
The Maternal and Child Health (KIA) program in Sigi Regency, Central Sulawesi Province, requires a comprehensive evaluation to ensure the effectiveness and sustainability of health interventions. This qualitative literature review aims to examine appropriate evaluation methods for the KIA program through an analysis of scientific literature. Literature was collected using keywords such as "evaluation methods," "maternal and child health program," and "Sigi Regency," focusing on publications from the last 10 years. Deductive content analysis identified relevant evaluation methods: technology-based information systems, community education through the KIA Handbook, improving healthcare workers' performance through training and operational funding, enhancing the quality of antenatal services, inter-agency collaboration, and formal evaluation models such as CIPP and the logic model approach. Key challenges include limited technological infrastructure, uneven distribution of healthcare workers, and lack of inter-agency coordination. This study recommends an integrated approach combining technology, education, human resources, service quality, and cross-sector collaboration to optimize the KIA program in Sigi. Future field research is needed to validate findings and formulate specific policies.